30.3k views
4 votes
Please help me because I got the answer wrong. ​

Please help me because I got the answer wrong. ​-example-1
User Piacenti
by
5.4k points

1 Answer

3 votes


\cfrac{1}{3}x^2~~ = ~~\cfrac{4}{27}\implies \cfrac{x^2}{3}~~ = ~~\cfrac{4}{27}\implies x^2=\cfrac{(3)4}{27}\implies x^2=\cfrac{12}{27} \implies x=\pm\sqrt{\cfrac{12}{27}} \\\\\\ x=\pm\cfrac{√(12)}{√(27)} \implies x=\pm\cfrac{√(2^2\cdot 3)}{√(3^2\cdot 3)}\implies x=\pm\cfrac{2√(3)}{3√(3)}\implies x=\pm\cfrac{2}{3}

User Jasin
by
4.5k points